PENGUATAN DAN PENDAMPINGAN KOMPETENSI ASESMEN AUTENTIK PENALARAN TINGKAT TINGGI PADA GURU SAINS MTS JAWA BARAT - Ridwan Efendi; Nuryani Y Rustaman; Winny Liliawati; Suhara (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract The ability of junior high school science teachers in making item question to measure high order thinking skills is very low and relevanless between the items with science competence and the curiculum. Therefore, it is necessary to strengthen and guiding junior high school science teachers in the form of workshop. Workshop was carried out through three webinars of strengthening materials (science, learning and assessment, Analysis of Basic Science Competencies for SMP/MTs, and authentic assessment of high-level reasoning) and online mentoring using google classroom and WhatsApp Group for two weeks. To explore the competence of Science teachers in constructing high-level reasoning items, task-rubrics and questionnaire responses from participants to the workshop were used. Nine sets of Science test questions were produced as a product of the workshop. Of the 31 MTs Sains teachers, after the workshop it was detected that most (25) participants were able to compile high-quality science items (80%), some (20%) still needed continuous improvement. Based on the questionnaire, it is known that science teachers want to continue to improve their competence in understanding and constructing high-level reasoning problems.AbstrakKemampuan guru sains SMP dalam membuat butir soal untuk mengukur kemampuan berpikir tingkat tinggi sangat rendah dan kurang relevan antara butir soal dengan kompetensi sains dan kurikulum. Oleh karena itu perlu dilakukan penguatan dan pendampingan guru sains SMP dalam bentuk workshop. Workshop dilaksanakan selama lima minggu melalui tiga kali webinar penguatan materi (sains, pembelajaran dan asesmen, Analisis Kompetensi Dasar Sains SMP/MTs, dan Asesmen autentik penalaran tingkat tinggi) dan pendampingan secara daring menggunakan google classroom dan WhatsApp Group selama dua minggu. Untuk menggali kompetensi guru Sains dalam mengkonstruksi butir soal penalaran tingkat tinggi digunakan task-rubrik dan angket respon peserta terhadap workshop. Sembilan set soal tes Sains dihasilkan sebagai produk lokakarya. Dari 31 guru MTs Sains, setelah workshop terdeteksi bahwa sebagian besar (25) partisipan mampu menyusun butir soal IPA berkualitas tinggi (80%), sebagian (20%) masih perlu perbaikan berkelanjutan. Berdasarkan hasil angket diketahui bahwa guru sains ingin terus meningkatkan kompetensinya dalam memahami dan mengkonstruksi soal penalaran tingkat tinggi.